Schlesinger Nailed It! Assessing a Key Primary Pharmacodynamic Property of Phages for Phage Therapy: Virion Encounter Rates with Motionless Bacterial Targets - Stephen T. Abedon (MDPI AG, 2023)
Bacteriophages (phages) are viruses of bacteria and have been used as antibacterial agents now for over one-hundred years. The primary pharmacodynamics of therapeutic phages can be summed up as follows: phages at a certain concentration can reach bacteria at a certain rate, attach to bacteria that display appropriate receptors on their surfaces, infect, and (ideally) kill those now-adsorbed bacteria. Here, I consider the rate at which phages reach bacteria, during what can be dubbed as an 'extracellular search'. This search is driven by diffusion and can be described by what is known as the phage adsorption rate constant. That constant in turn is thought to be derivable from knowledge of bacterial size, virion diffusion rates, and the likelihood of phage adsorption given this diffusion-driven encounter with a bacterium. Here, I consider only the role of bacterial size in encounter rates. In 1932, Schlesinger hypothesized that bacterial size can be described as a function of cell radius (R, or R1), as based on the non-phage-based theorizing of Smoluchowski (1917). The surface area of a cell-what is actually encountered-varies however instead as a function R2. Here, I both provide and review evidence indicating that Schlesinger's assertion seems to have been correct.